Conselhos de Alimentação Escolar: análise dos impactos da atuação no Estado do Ceará - Oliveira, Áquila Matheus de Souza (2018)
The work has, as a general goal, analyze the performance of CAE in the state of Ceará, focusing in the activities that cherish for the attributions found in the Primer of School Feeding (BRASIL, 2015) and the guidelines of the law 11.947/2009. As specific goals, it has a) understand the position of social control performed by the CAE; b) investigate how the surveillance of CAE in schools and its comprehensiveness in the State; c) Understand how CAE acts in the warranty of oversight of Food and Nutrition Security, zeal for the menu and respect to the student's feeding habits; d) Understand how the CAE acts in the promotion of Feeding and Nutrition Education actions. The qualitative approach has supported the interviews of counselors through the 2013-2017 management and who remain at present date. For the appraisal of these interviews it was used the technical - methodological support of interviews and participant observation. The analysis of data was based in the perspective of field search and it was divided into three stages, as says Gil (2008): organization of data, categorization of data and the interpretation of the obtained data. Five counselors were interviewed and submitted to a questionnaire. By analyzing the discourse, it is possible to see that some of the problems are indeed of difficult solution. The issue of comprehensiveness. Menus that are not practiced at the schools. Other standoffs, pointed out by the actors of this students are the options of EAN never fulfilled by the schools, the lack of structure and support from the Secretariat of Education for the organization of activities to the CAE. Meanwhile, there are also evident conquers, such as: the SIGE of feeding; the end of outsourcing in schools; the greeting of the 30% of resources destined to family agriculture; school environment in the conversation circles with the students, talks with teachers, school managers and lunch ladies; visibility and support of the education secretaries; the oversight with schedule and regularity of the kitchens and conditions of stock, hygiene and food safety and quality of the offered products, as well as the collection with the school managers so that the elaborated menus can be practiced. Lastly, the work reflects on the existing divergences between what is presented in the legislation and primers and what is in fact practiced in the daily lives of the counselors.